Impacts on Protective Structures against Gravitational Mass Movements—Scaling from Model Tests to Real Events - Simon Berger; Robert Hofmann (Geosciences, 2022)
Gravitational mass movements such as rockfalls, landslides, rock avalanches, or debris flows are increasingly endangering settlement areas and infrastructure facilities in the Alpine region as a result of climate change. An essential component of counteracting the dangers of such events is the construction of suitable protective structures. However, the dimensioning of these protective structures requires in-depth knowledge of the impact process on the structure. Measurements of real large mass movements such as rock avalanches fail due to the large impact forces involved. For this reason, model tests have been carried out by different institutions in different countries in recent decades. An essential aspect of the study of gravitational mass movements using model experiments is scaling experimental results to real events. Therefore, in this study, a model experiment carried out at the University of Innsbruck was recalculated in the first step using the discrete element method (DEM). Subsequently, the experimental results and the numerical DEM model were scaled to a real event using scale factors and then compared again. The aim was to show how well the results of the model tests can be scaled to describe real events of rock avalanches.